The effect size analysis of process oriented guided inquiry learning (POGIL) model on cognitive aspects of science learning - Ilman, Eprian Nur; Putri, Aulia; Sianturi, Lidya Juliven; Ristanto, Rizhal Hendi; Isfaeni, Hanum (Assimilation: Indonesian Journal of Biology Education, 2024)
Process Oriented Guided Inquiry Learning (POGIL) model is designed to make students actively participate in study groups. The aim of this research is to analyze the effectiveness of the influence of the POGIL model in learning science on cognitive aspects or student learning outcomes. This research used a meta-analysis method with research subjects as many as 11 national articles with PRISMA guidelines. The guidelines for meta-analysis research include collecting data, calculating the effect size for each research subject, Assessing the impact of using POGIL model on learning outcomes which include cognitive aspects of students, Drawing conclusions. The results of this research showed that there was a difference between the experimental class and the control class regarding the cognitive aspects of science learning. POGIL model can improve science learning outcomes based on the results of the analysis. It is ranging from 9.43% for the lowest to the 37.18% for the highest with an average of 19.85%. The results of the effect size analysis showed that the POGIL learning model has a strong category with 1,794 in score. This showed that POGIL model can influence cognitive aspects and critical thinking skills.